Meta-linguistic awareness skills in Chinese-speaking children with hyperlexia: A single-case study - Luo, Lirong; Su, I-Fan (Frontiers in Psychology, 2023)
Purpose: The aim of the study is to examine the meta-linguistic awareness skills contributing to reading aloud in a Chinese-speaking child with hyperlexia. Method: Case study approach was used with one case of hyperlexia (TYH) and two control groups: typically developing (TD) children matched for chronological age (CA), and TD children matched for mental ability (MA). A battery of phonological, morphological, and orthographic awareness skill tests were administered. Results: Results from the modified t-test found that the hyperlexic child did not demonstrate advanced meta-linguistic awareness skills in comparison with the two control groups. On the contrary, TYH’s morphological awareness skills were even lower than the CA control group. Also, in the orthographic awareness test, TYH demonstrated weaker knowledge of character structure and components than the two control groups although his ability in the recognition of real words is intact. In addition, the predictability of orthographic awareness skill was comparable to the CA group with predicted score showed no difference to his obtained score, while TYH achieved a significantly higher reading score than what his morphological awareness skills should predict with reference to TD children of similar age; as well as what his phonological awareness skill predict with reference to the MA group. Conclusions: The findings suggest that TYH can achieve advanced reading ability with comparable phonological and orthographic awareness skill, despite his weakness in morphological awareness. It is concluded that the hyperlexic reading in Chinese might be achieved through the direct mapping between the whole character and the sound.